Florida Strawberry Growers Need More Early Yield to Improve Profitability - Feng Wu; Zhengfei Guan; Vance Whitaker (EDIS, 2018)
Fresh strawberries are a major US fruit crop. This 3-page fact sheet written by Feng Wu, Zhengfei Guan, and Vance Whitaker and published by the UF/IFAS Food and Resource Economics Department summarizes recent research on strawberry yield patterns and how they are predicted to affect profits. It is intended primarily for those involved in Extension, marketing, policy-making, production, and research related to the Florida strawberry industry. We believe that a better understanding of yield and price dynamics will be valuable to industry decision-makers. http://edis.ifas.ufl.edu/fe1032